2015
DOI: 10.3950/jibiinkoka.118.1220
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Analyses of 115 Patients with Peritonsillar Abscess

Abstract: The clinical data of 115 patients with peritonsillar abscess (98 men and 17 women) treated between May 2011 and March 2014 were analyzed. We examined 9 items; the age, sex, affected side, duration of hospitalization, method of drainage, smoking history, history of diabetes, antibacterial drugs used, and the isolated bacteria. The disease predominantly affected males in their 30s (27.8% of all the patients). The median duration of hospitalization was 7 days. In regard to the affected side, the right side was af… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 1 publication
3
5
0
Order By: Relevance
“…3,6,14 Similar to previous studies, bacteria were detected in 36%, including mixed infections. Reports of CLDM-resistant bacterial strains have increased recently, 3,[14][15][16] and our investigation also detected 17% strains that were CLDM-resistant. None of the strains were resistant to ABPC/SBT, suggesting good therapeutic effects of ABPC/SBT monotherapy.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…3,6,14 Similar to previous studies, bacteria were detected in 36%, including mixed infections. Reports of CLDM-resistant bacterial strains have increased recently, 3,[14][15][16] and our investigation also detected 17% strains that were CLDM-resistant. None of the strains were resistant to ABPC/SBT, suggesting good therapeutic effects of ABPC/SBT monotherapy.…”
Section: Discussionsupporting
confidence: 86%
“…Anaerobic bacteria have been isolated in approximately 30 of 60% cases, depending on facilities. 3,6,14 Similar to previous studies, bacteria were detected in 36%, including mixed infections. Reports of CLDM-resistant bacterial strains have increased recently, 3,[14][15][16] and our investigation also detected 17% strains that were CLDM-resistant.…”
Section: Discussionsupporting
confidence: 86%
“…7,13 Regarding the affected side, many reports have indicated that there is no difference between the left and right sides and that bilateral cases account for approximately 1 to 5%. [2][3][4][5][6]10,11 In our patients, the rate of bilateral cases was somewhat high (6.2%), which could be attributed to the fact that all patients underwent contrast-enhanced CT and had lesions precisely evaluated in the present study. We believe that bilateral cases are more common than those reported to date.…”
Section: Discussionmentioning
confidence: 84%
“…Examination items included the following: (1) age and sex, (2) affected side, (3) number of patients according to type classification, (4) abscess diameter, (5) proportion of type per age, (6) bacteriological test results, (7) drug resistance, (8) treatment method according to type and diameter of abscess, (9) state of drug usage, (10) recurrence rate, and (11) recurrence time. However, when examining items 3, 4, 5, and 8, bilateral abscesses were treated as two separate cases or two sides.…”
Section: Subjects and Examination Itemsmentioning
confidence: 99%
“…1,4 In young individuals, peritonsillar abscess is common. [8][9][10] Scarring of areas surrounding the tonsils and vulnerable tissues causes difficulty in removing the tonsils and achieving hemostasis during surgery. Among the present cases, 15 were treated at our hospital for peritonsillar abscess (aged 20-56 years), of which 13 (86.7%) were aged 20 to 39 years.…”
Section: Partial Correlation Coefficientmentioning
confidence: 99%